Upaya Meningkatkan Teknik Dasar Long Service Bulu Tangkis dengan Menggunakan Metode Drill pada Siswa Kelas VI MIN 4 Kebumen - Mokhamad Parmadi; Nur Rohman (Mathematics Education Study Program, 2025)
This study aims to improve the basic long service technique in badminton among sixth-grade students at MIN 4 Kebumen through the application of the drill method. The research employed Classroom Action Research (CAR) with two cycles, each consisting of planning, action, observation, and reflection stages. The study involved 26 students (9 boys and 17 girls) as subjects. The instruments used were skill tests, observation sheets, and documentation. The results showed a significant improvement in long service skills. The average student score increased from 48.25 in the pre-cycle to 52.10 in the first cycle and 77.17 in the second cycle. Furthermore, the percentage of students reaching the